Genetics of a tropical heart condition - Nature Research (16552612) (2016)
Endomyocardial fibrosis (EMF) is a condition affecting the heart muscle, restricting the heart’s ability to fill with blood. In countries around the equator in Africa, EMF is the fourth most common cause of heart disease in adults, yet it is rare in countries like the US. Researchers are still uncertain as to the causes of EMF, but poverty, malnutrition and infections seem to be risk factors. Potential genetic predisposition to the disease was raised in the 1950’s when physicians in Uganda noticed three times as many EMF presentations from Rwanda-Burundi immigrants compared to Ugandans. In 2014, an international team of researchers collaborated to investigate a potential genetic link to EMF and published their results in the journal Global Cardiology Science & Practice. Blood tests were run on 40 patients in Mozambique and 42 patients in Uganda, all diagnosed with severe EMF. These results were compared to those of 89 and 50 controls from each country, respectively, all matched for age and ethnic group. The cells in the human body have complex proteins on their surface called human leukocyte antigens (HLA). These surface proteins are inherited and play a role in helping the immune system distinguish the body’s own cells from foreign cells. There are many different types of HLAs; the ones an individual has depends on which ones they inherited. The team wanted to investigate whether EMF patients were more likely to have specific types of human leukocyte antigens (HLA) on their cells. They found that patients with severe EMF in Mozambique were more likely to have an HLA type called HLA-B*58 than controls from the same country. In Uganda, on the other hand, patients with severe EMF were more likely to have HLA-A*02:02 than controls from the same country. The researchers concluded that their data suggests that the HLA system may play a role in the complex pathway that leads to the development of EMF, making some individuals more genetically susceptible to the condition. Further research is required to understand the pathogenesis of EMF. “A better understanding of host susceptibility could provide important insights into the development of EMF, which in turn could inform early diagnosis and improve therapeutics for this devastating tropical cardiomyopathy,” the researchers conclude. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0